2020
DOI: 10.3390/jcm9061742
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Combination of Normal BMI with Elevated YKL-40 and Leptin but Lower Adiponectin Level Is Linked to a Higher Risk of Breast Cancer Relapse: A Report of Four-Year Follow-Up Study

Abstract: Adipokines are powerful agents involved in the development of obesity-dependent cancers. This prospective study aimed to investigate the association between pre-treatment body mass index (BMI) and serum YKL-40, leptin, and adiponectin concentrations as well as the plasma activity of tissue factor (TF) and the future prognosis of early, non-metastatic breast cancer (BrC) subjects. The serum levels of YKL-40, leptin, and adiponectin as well as plasma TF activity, anthropometric parameters, and clinicopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Undoubtedly, adiposity in obesity is the key influencer associated with the adverse progression of breast cancer. However, one clinical report showed increased numbers of cases of breast cancer recurrence concurrent with decreased survival in normal BMI breast cancer patients (BMI < 25 kg/m 2 ) with stage I and II disease, in comparison to obese or overweight BMI (BMI > 25 kg/m 2 ) patients [ 135 ]. Furthermore, another clinical report highlighted all the research studies demonstrating high BMI subjects with markedly improved immune-efficacy responses, following immune checkpoint blockade treatment in comparison to normal BMI subjects, despite the contradictory role of obesity in immunosuppression [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, adiposity in obesity is the key influencer associated with the adverse progression of breast cancer. However, one clinical report showed increased numbers of cases of breast cancer recurrence concurrent with decreased survival in normal BMI breast cancer patients (BMI < 25 kg/m 2 ) with stage I and II disease, in comparison to obese or overweight BMI (BMI > 25 kg/m 2 ) patients [ 135 ]. Furthermore, another clinical report highlighted all the research studies demonstrating high BMI subjects with markedly improved immune-efficacy responses, following immune checkpoint blockade treatment in comparison to normal BMI subjects, despite the contradictory role of obesity in immunosuppression [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is still no standardized alternative measure of body composition that considers age, sex, and the existence of varying ethnicities [ 137 ]. Hence, a well-planned clinical research study design with the proper timing of BMI determination (pre, peri, and post diagnosis as well as treatment), accounting for all the relevant covariables mentioned above, needs to be considered to find the answers for the relationship of obesity in carcinogenesis and cancer progression [ 135 , 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity may exacerbate estrogen production, lead to chronic subclinical inflammation, and increase circulating levels of proinflammatory proteins favoring cancer development (36). Bielawski's research showed that BMI is an independent predictor of survival, with overweight/ obese women being less prone to relapse (37). When we analyzed the BMI of patients belonging to different clinicopathological categories, we found a strong correlation between BMI and age.…”
Section: Discussionmentioning
confidence: 81%
“…This may reflect the upregulation of compensatory mechanisms in the setting of decreased adiponectin expression 74 . Increased adiponectin levels may be indicative of improved overall survival and disease‐free survival in breast cancer 73,76 . However, Obi et al.…”
Section: Methodsmentioning
confidence: 99%